2022
DOI: 10.14366/usg.21256
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous radiofrequency ablation of solitary hepatic metastases from colorectal cancer: risk factors of local tumor progression-free survival and overall survival

Abstract: Purpose: This study aimed to evaluate local tumor progression-free survival (LTPFS) and overall survival (OS) after percutaneous radiofrequency ablation (RFA) for solitary colorectal liver metastases (CLM) <3 cm and to identify the risk factors associated with poor LTPFS and OS after percutaneous RFA.Methods: This study screened 219 patients who underwent percutaneous RFA for CLM between January 2013 and November 2020. Of these, 92 patients with a single CLM <3 cm were included. LTPFS and OS were calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…For CLM, it has been shown that minimum ablation margins of at least 5 mm and ideally 10 mm are critical for prolonged local tumour progression-free survival, regardless of the thermal ablation modality used (RFA or MWA). 5,[12][13][14][15]17,18,[55][56][57][58] This is referred to as an A0 ablation, analogous to surgical resections with clear microscopic margins (R0) and is essential to provide local cure and serve as a surgical alternative, since the majority of intrahepatic micrometastases are within 1 cm of the gross tumour. 59 When a 10 mm minimal margin can be achieved, local tumour progression free-survival exceeds 95% and can offer a chance for local cure similar to surgery, without the associated morbidity.…”
Section: Ablation Marginsmentioning
confidence: 99%
See 1 more Smart Citation
“…For CLM, it has been shown that minimum ablation margins of at least 5 mm and ideally 10 mm are critical for prolonged local tumour progression-free survival, regardless of the thermal ablation modality used (RFA or MWA). 5,[12][13][14][15]17,18,[55][56][57][58] This is referred to as an A0 ablation, analogous to surgical resections with clear microscopic margins (R0) and is essential to provide local cure and serve as a surgical alternative, since the majority of intrahepatic micrometastases are within 1 cm of the gross tumour. 59 When a 10 mm minimal margin can be achieved, local tumour progression free-survival exceeds 95% and can offer a chance for local cure similar to surgery, without the associated morbidity.…”
Section: Ablation Marginsmentioning
confidence: 99%
“…Multiple studies have proven that the most important technical factor for local tumour control is ablation with adequate margins. For CLM, it has been shown that minimum ablation margins of at least 5 mm and ideally 10 mm are critical for prolonged local tumour progression‐free survival, regardless of the thermal ablation modality used (RFA or MWA) 5,12–15,17,18,55–58 . This is referred to as an A0 ablation , analogous to surgical resections with clear microscopic margins (R0) and is essential to provide local cure and serve as a surgical alternative, since the majority of intrahepatic micrometastases are within 1 cm of the gross tumour 59 .…”
Section: Ablation Marginsmentioning
confidence: 99%